Kebangkitan Ijtihad di Zaman Modern: Analisis Kontribusi Muhammad Abduh dalam Pembaharuan Hukum Islam - Rukmana Prasetyo; Ade Rahman Matondang; Sultoni Trikusuma; Abdullah Sani (Hikmah, 2023)
Entering the 19th century which is often called the period or the modern century, Islamic figures and leaders realized the weaknesses and causes of the decline of the Muslim community. It was as if they agreed that Muslims must rise from adversity and stagnation in thinking, especially regarding Islamic law and free themselves from blind obedience. This study aims to analyze the sequence of the ijtihad period from decline to revival, and analyze the contribution of Muhammad Abduh in the renewal of Islamic law. The research uses a qualitative research method based on literature study, the data source in this study analyzes the works of Muhammad Abduh, especially with regard to Islamic law. The research results explain that. The revival of Ijtihad in the Modern era began when it entered the 19th century, which was marked by movements against Western/foreign occupation of Islamic territories; knowledge movement and return to pure Islamic teachings; the movement to reinterpret the understanding and thought of Muslims; Ijtihad on completely new issues that arise as a result of the ongoing development of science and technology. Muhammad Abduh's contribution can be seen from his invitation to Muslims to use their minds optimally so that the Muslim community develops and its Islamic law develops as was done by our predecessors.